Roles of drying, size reduction, and blanching in sustainable extraction of phenolics from olive leaves - Safarzadeh Markhali, Fereshteh (2021)
It is now known that olive leaves contain a sizable portion of polyphenols and there is much research highlighting that these natural ingredients favorably exhibit bio-functional activities. In this regard, many studies have focused on the exploration of optimum conditions involved directly in the extraction process. These investigations, while being highly valuable, may somewhat cast a shadow over other contributing factors such as those involved in the preprocessing of leaves, including size reduction, drying, and blanching. The use of these unit operations under appropriate conditions, together with other benefits, potentially exert improved surface area, homogeneity, and diffusion/mass transfer which may help develop the liberation of target bio-compounds. The research work in this area, particularly size reduction, is relatively limited. Although in various experiments they are incorporated, not many studies have focused on them as the main predictor variables. The performance of further research may help ascertain the magnitude of their effects. Consideration of the operational parameters in preprocessing step is equally important as those in the processing/extraction step that may comparably influence on the extraction efficiency. This review provides an overview of the potential roles of drying, size reduction, and blanching in the extraction efficiency of phenolics from olive leaves.